The Outcomes of the Reforming Higher Education System in the Kurdistan Region - Saied Qadir Faqe Ibrahim,; Said Shams, (Technium Social Sciences Journal, 2020)
The main purpose of this paper is to explain the outcomes and tangible inputs of reforming of teaching and establishing a teaching quality assurance system. The article design takes on a mix-method is employed by applying qualitative methods in a series interviews carried out with five decision-maker polices in the Ministry of higher education institutions in the KRG and quantitative methods have been applied too; the data has been collected by questionnaire and the participations are teachers from Salahaddin University, the University of Sulaimani, the University of Duhok, Koya University and Soran University. The sample in this paper consists of 575 teachers from these institutions. The results of this exploratory paper shows that the outcomes of the reforming of teaching quality assurance principle which was not quite changes in content in the sides of quality of students, relationship between student-teacher, methods of teaching, learning and evaluation of students.